Quizizz: Science learning media in elementary school in developing critical thinking skills - Widi Harawi Rizqi Nasution; Amanda Syahri Nasution (Journal of Science Education Research, 2021)
The ability to use technology in the era of the Industrial Revolution 4.0 is something everyone should have. Likewise in the field of education, teachers and students can use technology as part of the media used during the learning process. Learning by utilizing technology as learning media is expected to give a pleasant, challenging, and interactive impression that contributes to the abilities of elementary school students. One of the abilities of elementary school students that are expected to develop is critical thinking skills. Critical thinking skills are the ability to observe, analyze, and evaluate previously acquired knowledge based on logical reasoning. Critical thinking skills can be developed with the help of learning media. One of the technology-based learning media that can be used is Quizizz. Quizizz is a web tool or smartphone-based application that can create interactive quizzes in the form of games used in the learning process both in and/or outside the class or in distance learning. Therefore, Quizizz is expected to contribute to the development of students’ critical thinking skills in elementary schools, especially in science learning.